First report of the genus Cratera (Platyhelminthes, Geoplanidae) in Argentina, with description of a new species and comments on the species of the genus - Negrete, Lisandro Hector Luis (2016)
A new species of land planarians of the genus Cratera is described. Cratera viridimaculata sp. n. was recorded in the Atlantic Forest Ecoregion, in north-eastern Argentina, and represents the first report of the genus Cratera outside Brazil. The new species is about 50 mm in length and externally characterized by a color pattern consisting of a light green olive pigmentation on the dorsum, stippled with dark gray fine spots, and dorsal eyes. Other features regarding the internal anatomy are the presence of a glandular margin, Cutaneous Muscular Index (CMI) of 10–13%, pharynx cylindrical, prostatic vesicle extrabulbar, tubular and C-shaped, with a proximal bifurcated portion, penis papilla protrusible with ejaculatory duct widened in its distal portion, and female atrium funnel-shaped. The new species is compared and discussed with its congeners.